Photo-Oxidative Degradation and Hydrolytic Degradation of Micro-Graphite Filled Poly(lactic acid) Composites - Mujtahid Kaavessina; Esa Nur Shohih; Sperisa Distantina; Fadilah Fadilah (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
In a specific range of electrical conductivity, poly(lactic acid)/PLA has the potential to be developed into environmentally friendly antistatic packaging after a modification process. PLA was blended in a mini single screw extruder at 180oC with different compositions of micro-graphite (0, 0.5, 1, and 1.5 %wt.). This report discusses the degradability of PLA composite, i.e., photo-oxidative degradation and hydrolytic degradation. The weight loss, thermal properties, and cross-section morphology of the tested specimens were monitored periodically. During the degradation test, micro-graphite could be released from the composite, leaving a rough surface and reducing the weight of the composite. Differential scanning calorimetry (DSC) test exhibited that the presence of micro-graphite did not influence the melting temperature of the composition studied. However, the onset temperature of the melting point showed a slight shift of about 2-4oC. Bulk crystallinity demonstrated a considerable dependence on the micro-graphite loading (0-1.5%wt). However, there were two contradictory phenomena after both degradation tests. UV exposure could stimulate the fragmentation of PLA chains, break the crystal structure and increase the embrittlement. Thus, crystallinity tended to decrease during photo-oxidative degradation. In hydrolytic degradation, degradation firstly occurred in the amorphous regions and was ongoing within the studied range of time (0-20 weeks). Thus, the bulk crystallinity of composite tended to increase.